Electrophysiological correlates of action observation treatment in children with cerebral palsy: A pilot study. Issue 11 (4th February 2020) - Quadrelli, Ermanno; Anzani, Anna; Ferri, Matteo; Bolognini, Nadia; Maravita, Angelo; Zambonin, Fabio; Turati, Chiara
Abstract: Action Observation Treatment (AOT) has been shown to be effective in the functional recovery of several clinical populations. However, little is known about the neural underpinnings of the clinical efficacy of AOT in children with Cerebral Palsy (CP). Using electroencephalography (EEG), we recorded µ rhythm desynchronization as an index of sensorimotor cortex modulation during a passive action observation task before and after AOT. The relationship between sensorimotor modulation and clinical outcomes was also assessed. Eight children with CP entered the present randomized controlled crossover pilot study in which the experimental AOT preceded or followed a control Videogame Observation Treatment (VOT). Results provide further evidence of the clinical efficacy of AOT for improving hand motor function in CP, as assessed with the Assisting Hand Assessment (AHA) and Melbourne Assessment of Unilateral Upper Limb Function Scale (MUUL). The novel finding is that AOT increases µ rhythm desynchronization at scalp locations corresponding to the hand representation areas. This effect is associated to functional improvement assessed with the MUUL. These preliminary findings, although referred to as a small sample, suggest that AOT may affect upper limb motor recovery in children with CP and modulate the activation of sensorimotor areas, offering a potential neurophysiological correlate to support the clinical utility of AOT.